Effect of Different Levels of Cinnamaldehyde on Haematological and Biochemical Blood Constituents of Vanaraja Chicken (Indian Journal of Animal Production and Management, 2024)
A total of 60 day old sexed-female Vanaraja  chicks were reared for 0-34 weeks of age. Birds  were divided randomly into three dietary treatments  composed of 20 birds per group with 5 replicates  each. The experimental treatments were fed: basal  diet T1, 2.5g of cinnamaldehyde T2, and 5g of  cinnamaldehyde T3 per kg feed. The blood sample  was taken on the 4th and 8th month to examine  haematological and biochemical parameters. At the  end of the experimental trial, it has been observed  that chicken fed with cinnamaldehyde had a lower  level of haemoglobin, Packed cell volume,  cholesterol, Low Density Lipoprotein, triglyceride,  and glucose. However, there was no significant  difference in High Density Lipoprotein among the  treatment groups. In conclusion, using  cinnamaldehyde as a dietary supplement helps in  the reduction of certain blood constituents of  Vanaraja birds.
Keywords: cinnamaldehyde; haematological; biochemical; Vanaraja chicken